Velocity 2016, Amsterdam, The Netherlands (O'Reilly Media, 2016)
"Velocity 2016 Amsterdam featured 73 prominent experts working at companies like SOASTA, Docker, CoScale, GitLab, AppDynamics, Fastly, LeaseWeb, Pivotal, Travis CI, Bekk Consulting, Acrolinx, Plumbr, and more to speak on all things related to building websites, apps, and services that are fast, scalable, resilient, and highly available. The conference was organized into four major themes: metrics and monitoring (topics included the Elastic stack, Kubernetes/Prometheus, and AMP); organizational infrastructure (how to onboard at scale, the Nudge theory for improving team performance, Yahoo's use of DevOPs to launch products at 1 billion user scale, etc.); UX performance improvement (a walk-through of PWA technologies, the rewards and challenges of Push, a deep dive into image and type optimization, etc.); and strategies for reimagining DevOps, security, and infrastructure (sessions on moving from MySQL to Aurora at AWS, new techniques for defending against bots, the story of how Komfo achieved 60X faster tests, the future of serverless software architecture, best practices for MySQL HA, and more)."--Resource description page.